How confident are general paediatricians at assessing and managing obesity in childhood?. (4th April 2011) - Wake, M; Turner, M J; Price, A; Sabin, M A; Davis, E; Baur, L A
Abstract : Aims: Determination of self-reported competencies in the management of obesity and its co-morbidities, relationships between these and relevant training, and relating these perceived competences to actual practice. Methods: 373 general Paediatricians from an Australian research network were invited to complete a multi-topic online questionnaire (with five topics, including obesity) detailing prior training in, and perceived competence in managing obesity and its co-morbidities. Data were also taken from a prospective audit on clinical practice within the research network. Results: 167/373 surveyed completed the obesity questions. The self-reported competencies in managing obesity and its co-morbidities are shown in table 1 . While 66% perceived they were competent in management of obesity only 20% felt competent at making a difference. Perceived competence in management of co-morbidities ranged from 64% (obstructive sleep apnoea) to 20% (dyslipidaemia). Few of the respondents had received specific skills training for obesity and few of those who were trained used the skills (table 2 ). For every skill that a paediatrician was trained in, their competency in managing obesity rose by 40% and in making a difference by 50%. In addition, for each additional co-morbidity they felt very/quite competent in managing, their competency in the above outcomes rose by 60% and 30% respectively. Of the 167 respondents, 127 had also participated in an audit on clinical practice. There were no significant associations between self-reported competencies or training, and the likelihood of recording height and weight or of recording an obesity diagnosis for obese children in actual practice. Conclusion: Most respondents did not feel competent at making a difference to an obese child's weight. There were also low levels of reported competence in managing important comorbidities. Training was associated with greater perceived competence at management of an obese child's weight but levels of training were low and use of training even lower. The perceived competence, confidence and training were not associated with actual practice.